2005
DOI: 10.1074/jbc.m409918200
|View full text |Cite
|
Sign up to set email alerts
|

STAT5B-mediated Growth Hormone Signaling Is Organized by Highly Dynamic Microtubules in Hepatic Cells

Abstract: In the last decade, the notion that microtubules are critical to the spatial organization of signal transduction and contribute to the transmission of signals to downstream targets has been proposed. Because the STAT5B transduction and transcription factor is the major STAT protein activated by growth hormone stimulation in hepatocytes and is a crossroads between many signaling pathways, we studied the involvement of microtubules in STAT5B-mediated growth hormone signaling pathway in the highly differentiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…Induction of cytoskeleton structuring has been described with many cytokines and chemokines but mostly over longer time spans. Pioneering studies on prolactin receptor (35), growth hormone receptor (36), and epidermal growth factor receptor (37) have suggested that machineries carried by the cytoskeleton might be involved in STAT5 and pSTAT5 distribution and proposed that rapid organization was involved. Here, in our study, we used super-resolution optical microscopy to describe in detail how radial microtubules are formed within a few min of IL-7 activation, bridging plasma and nuclear membranes across the narrow cytoplasm of CD4 T-lymphocytes.…”
Section: Sted Microscopy Analysis Of Il-7-induced Membrane Microdomaimentioning
confidence: 99%
“…Induction of cytoskeleton structuring has been described with many cytokines and chemokines but mostly over longer time spans. Pioneering studies on prolactin receptor (35), growth hormone receptor (36), and epidermal growth factor receptor (37) have suggested that machineries carried by the cytoskeleton might be involved in STAT5 and pSTAT5 distribution and proposed that rapid organization was involved. Here, in our study, we used super-resolution optical microscopy to describe in detail how radial microtubules are formed within a few min of IL-7 activation, bridging plasma and nuclear membranes across the narrow cytoplasm of CD4 T-lymphocytes.…”
Section: Sted Microscopy Analysis Of Il-7-induced Membrane Microdomaimentioning
confidence: 99%
“…For example, disruption of dynein motor activity by overexpressing dynamitin impaired the accumulation of p53 in the nucleus following DNA damage (71). In addition, overexpression of p50/dynamitin impaired the nuclear accumulation of STAT5B after growth hormone induction (72), as well as the nuclear translocation of the glucocorticoid receptors after ligand stimulation (73). Because our results have shown that overexpression of dynamitin blocked Smad2 nuclear translocation after TGF␤ treatment, dynein-dependent intracellular events also appear to be required for TGF␤/Smad2 downstream effects.…”
Section: Discussionmentioning
confidence: 99%
“…MT protein fractionation was then validated by checking that the signaling and transcription factor STAT5B bound specifically to the labile MT fraction ( Fig. 2A) and that the latter was not contaminated with soluble proteins, as STAT5A remained exclusively in the cytosol (36). The stable MT fraction was enriched in modified tubulin as shown by the distribution of the acetylated and detyrosinated tubulins.…”
Section: Markers Of Autophagosome Formation Are Specifically Recruitementioning
confidence: 99%
“…To test this hypothesis, we performed cell fractionation experiments in which we purified the proteins associated with labile MTs and with stable MTs (36). Cells were permeabilized using low saponin concentrations to avoid artifactual LC3 aggregation (supplemental Fig.…”
Section: Markers Of Autophagosome Formation Are Specifically Recruitementioning
confidence: 99%